Short-term intake of Yellowstripe Scad versus salmon did not induce similar effects on lipid profile and inflammatory markers among healthy overweight adults despite their comparable EPADHA content - Wei, Lin Chang; Azlan, Azrina; Md Noor, Sabariah; Ismail, Irmi Zarina; Su, Peng Loh (MDPI AG, 2021)
Yellowstripe scad (YSS) have comparable eicosapentaenoic acid and docosahexaenoic acid (EPA+DHA) content to salmon. We aimed to compare the effects of YSS and salmon on lipid profile and inflammatory markers. A randomized crossover trial with two diet periods was conducted among healthy overweight (with BMI 23.0–27.4 kg/m2) Malaysian adults aged 21–55 years. Steamed whole YSS fish (≈385 g whole fish/day) or salmon fillets (≈246 g fillet/day) were given for eight weeks (3 days per week), retaining approximately 1000 mg EPA+DHA per day. Diets were switched after an 8-week washout period. Fasting blood samples were collected before and after each diet period. A total of 49 subjects participated in the intervention (35% male and 65% female; mean age 29 (7) years). YSS did not induce any significant changes in outcome measures. However, the consumption of salmon as compared with YSS was associated with reduction in triglycerides (between-group difference: −0.09 mmol/1, p = 0.01), VLDL-cholesterol (between-group difference: −0.04 mmol/1, p = 0.01), atherogenic index of plasma (between-group difference: −0.05 mmol/1, p = 0.006), and IL-6 (between-group difference: −0.01 pg/mL, p = 0.03). Despite their comparable EPA+DHA content, short-term consumption of salmon but not YSS induced significant changes in lipid profile and inflammatory markers. Larger clinical trials are needed to confirm the findings.